Box-Behnken Design-Based Optimization of Treatment Parameters for Soluble Reactive Phosphorus Removal of Synthetic Wastewater using Immobilized Spirulina platensis Beads - Calajate, Sean Andre D.; Robles, Francis Edric M.; Rojas, Maria Francesca I.; Tolentino, Tristan Josef A.; Masongsong, Angela Nicole S.; Estrellado, John Ray C. (Future Science / FSH-PH Publications, 2025)
Soluble reactive phosphorus (SRP), a bioavailable phosphorus form, contributes to over-eutrophication by stimulating uncontrolled algal growth. This study aims to determine the optimum treatment parameters for the SRP removal from synthetic wastewater using the alginate-immobilized cyanobacteria Spirulina platensis. S. platensis was immobilized in alginate beads with varying alginate concentrations (2.5%, 3%, and 3.5% w/v), and subjected to varying operation time (1, 2, and 3 days), and bead dosage (1.5, 2, and 2.5 beads/mL) for SRP removal using Box-Behnken experimental design. Resulting model indicated a strong predictive relationship with R2 = 0.9253 and p = 0.0212. Main effects of bead dosage (p = 0.01372), its quadratic effect (p = 0.01643), and its interaction with alginate concentration (p = 0.00465) were found to be statistically significant. Predicted optimum parameters (2.5% w/v alginate, 3 days, and 1.5 beads/mL) were validated and resulted in a lower SRP removal of 92.80 ± 0.73% with a percent error of 5.22% relative to a predicted SRP removal of 97.91%. Extrapolation of the prediction model to 100% outside the experimental region was verified resulting in SRP removal of 97.39 ± 0.08% with a percent error of 2.61% was achieved by adjusting the operation time to 3.4 days. The study shows promising potential of immobilized S. platensis beads in addressing over-eutrophication through significant phosphorus reduction.